Comrades’ power: Student representation and activism in universities in Kenya (Journal of Student Affairs in Africa, 2021)
In the last decade, student politics and governance of universities in Kenya and in other African countries have undergone a tremendous transformation. The unprecedented expansion and massification of public universities, the introduction of ‘Module 2’ programmes, the admission of private, ‘parallel’ and ‘school-based’ students, and the substantial increase in private universities have impacted on the governance of the institutions and student politics in different ways. In this context, this article explores student involvement in university governance and describes the structure of students’ unions in Kenyan universities in comparison with students exercising ‘comrades’ power in universities in Kenya.
Keywords: Higher education; student politics; student activism; student unionism; university governance; representation